Model of assessment of requirements of privacy, security and quality of service for mobile medical applications - Guillen Pinto, Edward Paul; Ramirez López, Leonardo; Cifuentes Sanabria, Yuli Paola (Universidad y Salud, 2017)
Introduction: The development of mobile technologies has facilitated the creation of mHealth applications, which are considered key tools for safe and quality care for patients from remote populations and with lack of infrastructure for the provision of health services. The article considers a proposal for an evaluation model that allows to determine weaknesses and vulnerabilities at the security level and quality of service (QoS) in mHealth applications. Objective: To carry out an approximation of a model of analysis that supports the decision making, concerning the use and production of safe applications, minimizing the impact and the probability of occurrence of the risks of computer security. Materials and methods: The type of applied research is of a descriptive type, because each one details the characteristics that the mobile health applications must have to achieve an optimum level of safety. The methodology uses the rules that regulate applications and mixes them with techniques of security analysis, using the characterization of risks posed by Open Web Application Security Project-OWASP and the QoS requirements of the International Telecommunication Union-ITU. Results: An effective analysis was obtained in actual current applications, which shows their weaknesses and the aspects to be corrected to comply with appropriate security parameters. Conclusions: The model allows to evaluate the safety and quality of service (QoS) requirements of mobile health applications that can be used to evaluate current applications or to generate the criteria before deployment.